TRAJECTORIES OF KIDNEY FUNCTION AND ASSOCIATED FACTORS AMONG COMMUNITY-DWELLING OLDER JAPANESE: THE KUSATSU STUDY. (11th November 2018) - Kaito, S; Taniguchi, Y; Kitamura, A; Seino, S; Amano, H; Yokokawa, H; Fujiwara, Y; Shinkai, S
Abstract: Background: Chronic kidney dysfunction is a well-known risk factor for cardiovascular disease and mortality. However, no study reported trajectory patterns of kidney function in later life. This prospective study aimed at examining age-associated changes in serum creatinine level (SCr) by sex, classifying trajectory patterns of SCr, and identifying associated factors. Methods: We collected data from annual geriatric health checkups (GHC) conducted during 2002 through 2017 in Kusatsu, Gunma prefecture, Japan. 1990 adults aged 65–90 years (mean age, 71.0 years; women, 57.0%) participated in the GHC at least once during the period and total observation number was 9291. To those data we applied the mixed-effects model, group-based semiparametric mixture model, and Chi-squared test and analysis of variance. Results: Men showed approximately 0.2mg/dL higher SCr than women. We identified three trajectory patterns of SCr and denoted as high, middle, and low trajectory groups. Proportions of each groups were 5.4%, 41.0% and 53.6% for men, and 5.4%, 33.5%, and 61.1% for women. Those in the high trajectory group tended to have history of lifestyle-related disease including hypertension (p<.001) and cardiovascular disease (p=.002); this stood out in men. More people in the high trajectory group of SCr had consulted hospital regularly (79.0% vs 65% for the middle, 70.9% for the low). Conclusion: The present findings imply the prevention/control of Noncommunicable Diseases from younger ages is important for good kidney function in later life. 20% of persons in the high trajectory group didn't consult doctors periodically, while they had a higher risk for renal insufficiency.